Upaya Menanamkan Kesadaran Lingkungan melalui Strategi Pembelajaran Contextual Teaching and Learning (CTL) pada Program Paket A di PKBM Budi Utama Surabaya - Zharfana, Afina Nelish; Nugroho, Rivo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
Education plays a very important role in giving birth to a generation that is aware of the environment and able to act sustainably. The Contextual Teaching and Learning (CTL) approach has been integrated into the Package A CLC Budi Utama Surabaya program. The aim of this research is to analyze and describe efforts to instill environmental awareness through Contextual Teaching and Learning (CTL) learning strategies in the Package A program at CLC Budi Utama Surabaya. The research method used is a qualitative approach with data collection through observation, interviews and documentation. The research results show that CTL learning through river tracing activities is effective in increasing students' awareness of the importance of protecting the environment and understanding river ecosystems. This learning strategy, from planning to evaluation, makes a significant contribution to environmental education and the formation of sustainable behavior. Thus, the integration of CTL in environmental education at CLC Budi Utama Surabaya brings great benefits to students in preparing for a better future.